Genetic information, intimacy and discriminaton - Sánchez Urrutia, Ana Victoria (Acta Bioethica, 2002)
There are many advantages due to genetic tests. But genetic information, if badly applied, may affect personal and family intimacy or even arouse discrimination. Therefore, data derived from a person’s and his family’s genome are confidential; these should be subject to adequate measures of security, should be used only according to the purposes for which they were obtained and they should not be disclosed to third parties, except if the person involved gives his explicit consent or in virtue of a juridical mandate. Anyway, the Universal Declaration on the Human Genome and Human Rights and the European Council have given a similar opinion.